2022
DOI: 10.14715/cmb/2021.67.4.31
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the clinical efficacy of leuprolide acetate in the treatment of obese patients with endometriosis and its role on the expression of MIF gene

Abstract: Endometriosis is an invasive but benign disease of women that develops in endometrial glands outside the endometrium and uterine muscle. It affects about 15-20% of women of childbearing age. One effective way to treat endometriosis is to use GnRH agonists, which inhibit estrogen production. However, one of the possible side effects of this treatment is obesity and BMI increasing, which is a concern for some patients. This study investigated the role of leuprolide acetate in treating overweight patients (BMI≥30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Endometriosis refers to the presence of endometrium tissue outside the uterine cavity caused by local lesions, its occurrence and endometrium species, blood countercurrent, body cavity metaplasia and so on. There is a certain relationship (12)(13). Surgery is one of the effective means for treating this disease, which can effectively remove the lesions and relieve the symptoms of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Endometriosis refers to the presence of endometrium tissue outside the uterine cavity caused by local lesions, its occurrence and endometrium species, blood countercurrent, body cavity metaplasia and so on. There is a certain relationship (12)(13). Surgery is one of the effective means for treating this disease, which can effectively remove the lesions and relieve the symptoms of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, their proliferative activity is markedly increased ( Jiang and Wu, 2012 ), leading to neovascularization and the establishment of endometrial implants, which leads to the development of the disease and further malignant progression. Compared to that of healthy controls, the expression level of the anti-apoptotic gene B-cell lymphoma 2 (Bcl-2) is significantly elevated in the ectopic endometrium of patients with EMs ( Agic et al, 2009 ; Jiang R. et al, 2020 ), whereas that of the pro-apoptotic genes p53 and caspase-3 is decreased ( Sang et al, 2019 ; Duan R. et al, 2020 ; Zhang and Zhao, 2023 ). Cyclin D1 and cyclin E2 are key regulatory proteins that control the transition from the G1 phase into the S phase during the cell cycle ( Zabihi et al, 2023 ), and the expression of cyclin D1 mRNA has been shown to be significantly elevated in ectopic endothelial tissues compared to that in normal and eutopic endothelium ( Pellegrini et al, 2012 ).…”
Section: Possible Associations Of Adiponectin With the Pathogenesis O...mentioning
confidence: 99%
“…It is clear from the studies discussed above that a personalized medicine approach to EAP will be essential to reduce the time to successful treatment and the harm associated with unsuccessful therapeutic approaches. Although some recent studies have stratified/excluded participants on the basis of stage of endometriosis [39][40][41][42][43] or BMI [44], to date, no studies have stratified on the basis of pain characteristics. Questionnaire measures and potentially psychophysical assessments may help to identify underlying pain mechanisms and thus inform clinical trial design [45].…”
Section: Future Workmentioning
confidence: 99%